[tex]A.-2\frac{1}{3} \cdot(-\frac{3}{7} )=-\frac{7}{3} \cdot(-\frac{3}{7} )=\frac{\not7}{\not3} \cdot\frac{\not3}{\not7} =1[/tex]
[tex]B.-\frac{2}{4} \cdot1\frac{1}{2} =-\frac{\not2}{4} \cdot\frac{3}{\not2} =-\frac{1}{4} \cdot3=-\frac{3}{4}[/tex]
[tex]\boxed{C. }0,6\cdot(-1\frac{2}{3})= \frac{3}{5} \cdot(-\frac{5}{3} )=-\frac{\not3}{\not5} \cdot\frac{\not5}{\not3} =-1[/tex]
[tex]D.-4\frac{2}{3} \cdot3\frac{2}{3} =-\frac{14}{3} \cdot\frac{11}{3} =-\frac{14\cdot11}{3\cdot3} =-\frac{154}{9} =-17\frac{1}{9}[/tex]
[tex]\boxed{E.}-10\cdot0,1=-10\cdot\frac{1}{10} =-1[/tex]